Salafis and Social Media: The Emergence of Islamic Populism in Indonesia - Muary, Rholand; Susanti, Neila; Atikah, Puteri (Jurnal Sosiologi Agama, 2024)
The development of the Salafism movement in Indonesia is supported by the digitalization of their preaching, even though previously this group claimed to be Puritan, rejected modernization and was known to be strict in interpreting the Koran and hadith. This article explains how Salafi preaching is increasingly spreading on social media with an Islamic populism approach based on political economy. Salafists claim that the digitalization of their preaching can be accepted by society, especially young people in the upper middle class, as evidenced by the millions of people following their social media accounts. This research data was collected through in-depth interviews with Salafi figures and managers of their digital da'wah channels, namely Rasyaad TV in Medan and Surau TV in Padang, and observing content from Salafi's social media accounts. The findings of this research show that Islamic populism is developing and is characterized by the Salafist movement adapting to developments in the digital world. They promote their ideology through Instagram, YouTube, and satellite TV channels. Even though in the early days, their da'wah tended to be more conventional and limited to the Salafi Mahjab community, now it is open to anyone and anywhere. In packaging Salafi preaching content, this movement also adapts to local (Minangkabau) culture, so the local community can accept it. Salafis are also starting to show their support for the democratic system by participating in general elections even though they previously strongly rejected the democratic political system in Indonesia. These findings could have implications for the new Islamic populism movement with the struggle for digital space as the spearhead of da'wah to strengthen Salafi religious ideology as well as negotiate the political system that applies to Salafi congregations in Indonesia